EFL Students’ Use of Technology in English Lesson in The Digital Era - Arigusman, Anggi; Purnawarman, Pupung; Suherdi, Didi (Indonesian Journal of Curriculum and Educational Technology Studies, 2018)
Various informations and knowledge including English lesson can easily be accessed. It gives a large opportuniy to the students to take benefts from the use of technology to up grade their English ability. However, most of EFL students seem only use technology for entertainment needs rather than for learning English. Therefore, the objectives of this research are to investigate the kinds of technology tools used by high school students and their beliefs toward the use of technology in English lesson. Mix method approach is used in this research to gain more comprehensive and representative data. The results show that there are eight activities that involve fve kinds of technology that the students frequently used. Those tools are MP3 player, internet browser, cellphone, social networking site, and television. All respondents agree that the use of technology in English lesson is eﬀective. Some advantages of using technology in English lesson appear in this research. However, some barriers or problems also found. The most disturbing barrier faced by the students is the access to internet. They also lack of information of useful technology tools which are possible to be used in English lesson. Abstrak Berbagai informasi dan ilmu pengetahuan termasuk pelajaran bahasa Inggris dapat diakses dengan mudah. Hal itu memberikan kesempatan yang besar pada siswa untuk memanfaatkan teknologi guna meningkatkan kemampuan bahasa Inggris mereka. Namun kebanyakan siswa EFL sepertinya lebih cenderung memanfaatkan teknologi untuk sekedar hiburan daripada untuk mengasah bahasa Inggris mereka. Oleh karena itu, tujuan penelitian ini adalah untuk menginvestigasi jenis-jenis teknologi yang digunakan oleh siswa SMA dan persepsi mereka terhadap penggunaan teknologi dalam pelajaran bahasa Inggris. Pendekatan mixed method digunakan dalam penelitian ini untuk memperoleh data yang lebih komprehensif dan representatif. Hasil penelitian ini menunjukan bahwa ada delapan aktiftas siswa yang melibatkan teknologi yang sering mereka gunakan. Yaitu MP3 player, internet browser, telepon seluler, situs jejaring sosial, dan televisi. Seluruh responden setuju bahwa penggunaan teknologi dalam pelajaran bahasa Inggris sangat efektif. Beberapa keuntungan pemanfaatan teknologi dalam pelajaran bahasa Inggris ditemukan dalam peneitian ini. Akan tetapi beberapa kendala juga ditemukan. Kendala yang paling mengganggu yang dihadapi oleh para siswa adalah akses terhadap fasilitas internet. Mereka juga kekurangan informasi tentang jenis-jenis produk teknologi yang berguna untuk digunakan dalam pelajaran bahasa Inggris. Keywords:  EFL students; English lesson; use of technology; internet